Integrating Local Wisdom and Policy Strategies for a Sustainable Blue Economy: The Case of Bengawan River Society in Bojonegoro City - Dwi Pranidya, Cici; Rohma, Mamluatur; Noer Laily, Raviqa (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2025)
The blue economy is a way of thinking about sustainable development that focuses on using water resources to boost the economy, promote health, and protect ecosystems. The Bengawan River is one of the longest rivers in Java. It is very important to the community's social and economic life, both through farming and fishing and through ecotourism. But pollution, environmental damage, and overexploitation have put the region's ecological and economic sustainability at risk. The Bengawan community, on the other hand, has local knowledge that has been passed down through the years about how to keep nature in balance. For example, they have a tradition of working together to clean the river and regulations about how to use water. This study seeks to evaluate the feasibility of incorporating indigenous knowledge into blue economy policy frameworks to attain ecological sustainability while enhancing the welfare of the Bengawan community. The research employs a qualitative methodology featuring descriptive analysis, collecting data through field observations, stakeholder interviews, and a literature evaluation pertaining to blue economy policy. The study's findings demonstrate that the local wisdom of the Bengawan community possesses ecological value consistent with the tenets of the blue economy; yet, it has not been effectively incorporated into government policy. This integration necessitates adaptable policy measures that incorporate community engagement, rules grounded in local values, and endorsement of sustainable empowerment initiatives. This study offers a conceptual contribution through a blue economy policy model rooted in local wisdom, alongside practical recommendations for local governments and stakeholders to ensure the sustainability of the Bengawan River in Bojonegoro.